Effect of CSR implementation and crisis events in business on the financial management of SMEs - Dvorský, Ján; Švihlíková, Ilona; Kozubíková, Ľudmila; Frajtova Michalíková, Katarína; Balcerzak, Adam P. (Technological and Economic Development of Economy, 2023)
The financial management of a business is an integral part of strategic management. Small and medium-sized enterprises (SMEs) are vulnerable to the presence of crisis events in the business environment. In this context, senior managers and owners need to react promptly to emerging changes in a given business segment. The aim of the article is to quantify the effect of crisis events in business and firm’s CSR implementation in business on the financial performance in the SMEs. The empirical research incorporated 1,090 SMEs in the business environment of four Central European countries. The research hypotheses were evaluated using structural equation modelling. The empirical findings confirmed the positive impact of CSR implementation in the enterprise on its financial management. The research results did not confirm the negative effects of crisis events in business on the financial management. Crisis phenomena have direct effects on the sustainability of the enterprise; the organizational activities of the enterprise; the functioning of the enterprise in the market and the management of the enterprise. The findings are used as a basis for the preparation of strategic projects of national and international policies helping to cope with crisis phenomena in the business environment of the SME segment.